Visionary Materialism in the Early Works of William Blake - Green, M. author. aut Link
X, 218 p.
Keywords: Incorporating the most recent discoveries concerning Blake's heritage and cultural context, Visionary Materialism in the Early Works of William Blake: The Intersection of Enthusiasm and Empiricism proposes a radical new reading of his early works, that sees them taking enlightenment ideas to heights never dreamed of by Locke and Priestley. Drawing on a careful analysis of key figures from both sides of the enlightenment/counter-enlightenment divide (including Boehme, Swedenborg, the Moravians, Lavater, Brothers, Erasmus Darwin), the discussion traces an alternative tradition that disrupts previous assumptions about important aspects of Blake's thought.